The book as a dynamic system for the commodification of ideas and cultural expressions - Weedon, Alexis (Primerjalna književnost, 2012)
Today, the book is challenged by the Internet as a source of information, and by other media as a vehicle for national culture, and yet it retains its privileged place as a valued and venerated vehicle for literary culture. Through an exploration of contemporary changes in publishing set against a historical understanding of the conceptual origins of copyright, I propose a redefinition of the book. I argue that the book is a dynamic system for the commodification of ideas and cultural expressions. As a system rather than a material object the book packages, stores, verifies, gatekeeps, permits trade by allowing transference of ownership, and verifies by documenting previous ownership of texts on which its ideas are built. Through this system creative, artistic, innovative, and cutting edge scientific ideas reach an audience. This is where its economic value and cultural worth lies.
Keywords: knjižni sistem; založništvo; ekonomski kapital; kulturni kapital; avtorske pravice; e-knjiga; ekonomsko založništvo